Cancer-associated mesenchymal stem/stromal cells: role in progression and potential targets for therapeutic approaches - Hazrati, Ali; Malekpour, Kosar; Mirsanei, Zahra; Khosrojerdi, Arezou; Rahmani-Kukia, Nasim; Heidari, Neda; Abbasi, Ardeshir; Soudi, Sara (Frontiers in Immunology, 2023)
Malignancies contain a relatively small number of Mesenchymal stem/stromal cells (MSCs), constituting a crucial tumor microenvironment (TME) component. These cells comprise approximately 0.01-5% of the total TME cell population. MSC differentiation potential and their interaction with the tumor environment enable these cells to affect tumor cells' growth, immune evasion, metastasis, drug resistance, and angiogenesis. This type of MSC, known as cancer-associated mesenchymal stem/stromal cells (CA-MSCs ( interacts with tumor/nontumor cells in the TME and affects their function by producing cytokines, chemokines, and various growth factors to facilitate tumor cell migration, survival, proliferation, and tumor progression. Considering that the effect of different cells on each other in the TME is a multifaceted relationship, it is essential to discover the role of these relationships for targeting in tumor therapy. Due to the immunomodulatory role and the tissue repair characteristic of MSCs, these cells can help tumor growth from different aspects. CA-MSCs indirectly suppress antitumor immune response through several mechanisms, including decreasing dendritic cells (DCs) antigen presentation potential, disrupting natural killer (NK) cell differentiation, inducing immunoinhibitory subsets like tumor-associated macrophages (TAMs) and Treg cells, and immune checkpoint expression to reduce effector T cell antitumor responses.Therefore, if these cells can be targeted for treatment so that their population decreases, we can hope for the treatment and improvement of the tumor conditions. Also, various studies show that CA-MSCs in the TME can affect other vital aspects of a tumor, including cell proliferation, drug resistance, angiogenesis, and tumor cell invasion and metastasis. In this review article, we will discuss in detail some of the mechanisms by which CA-MSCs suppress the innate and adaptive immune systems and other mechanisms related to tumor progression.